(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sarjito S, Amalia R, Sabdaningsih A. 2022. Screening of sponge-associated bacteria to control vibriosis in vannamei shrimp (Litopenaeus vannamei). Biodiversitas 23: 5333-5341. An intensive shrimp culture with a high stocking density causes a higher chance of vannamei shrimp being infected with diseases. The most frequent disease is caused by Vibrio sp. Vibrio might cause a severe production loss in the shrimp culture, leading to larvae and mature stadium mortality at 50%. Therefore, a study on the alternative management of vibriosis disease using biocontrol agents is urgently needed. The sponge is a marine invertebrate that provides as a shelter for microbes to live and symbiosis with the animal. An evident ability of sponge-associated bacteria to produce antimicrobial compounds can be exploited as a biodegradable bio-agent, potentially as a solution to control vibriosis disease in a shrimp. This research aimed to isolate sponge-associated bacteria with vibriosis antibacterial potential. Sampling was done in Tulamben, Bali and Panjang island, Jepara, Indonesia with six sampling sites consisting of 15 sampling points. Moreover, vibriosis bacteria were provided by the laboratory of fish disease at Balai Besar Perikanan Budidaya Air Payau (BBPBAP) Jepara. Totally, 24 and 47 pure cultures were successfully isolated using Zobell 2216E agar medium from Tulamben, Bali and Panjang Island, Jepara respectively. The isolates were tested for antibacterial assay using plug agar diffusion methods. The top eight potential isolates were found in isolate B6.3C, B6.3D, B6.4E, B9.3C, PA.1, PA.4, PC.3, and PH.1 against Vibrio vulnificus, V. anguillarum, V. alginolyticus, V. parahaemolyticus, however there was no activity in V. harveyi. The molecular method was carried out to identify those potential isolates using universal primer 16S rRNA. The BLAST homology showed that all potential antibacterial isolates belong to the family Bacilllaceae, such as Bacillus cereus, Virgibacillus salarius, B. aerius, B. paramycoides, B. thuringiensis, and B. altitudinis. Further research will be carried out on microencapsulation and in vivo tests.